Use of Additives in the Production of Silage with Plantain Rachis (Musa paradisiaca) - Cevallos-López, Verónica Carolina (2025)
Technological innovations enable the recycling of plantain rachis, which is typically discarded as waste. This study aims to evaluate the use of additives (lactic acid bacteria, efficient native microorganisms, and Gliricidia sepium) in the production of silage from plantain rachis (Musa spp) at different preservation times (1 and 6 months). Sixteen microsilos of 1 kg each were prepared for each preservation time, and the following parameters were determined: crude protein (PB), crude fiber (FB), ash, ether extract (EE), and nitrogen-free extract (ELN). The treatments used were: T1 Control, T2 SiloBacter®, T3 Gliricidia sepium, and T4 EM.1®. A completely randomized design with sampling over time was employed, and variance analysis was conducted with p<0.05 using Tukey's significance test in RStudio. The addition of Gliricidia sepium improved the nutritional composition of the silage, showing higher values at the first month for ELN (38,85%), FB (38,84%), ash (19,11%), and EE (2,74%). The T1 Control had the highest PB concentration (8,24%). At six months, T3 showed the highest nutritional value in PB (7,38%), EE (2,74%), ELN (38,35%), and the lowest values in FB (38,41%) and ash (20,80%). It is concluded that the use of plantain rachis silage with the addition of Gliricidia is a good alternative as a ruminant feed supplement six months post-production. Transforming rachis into silage significantly contributes to the resilience of agro-food systems.